Upaya Menumbuhkan Jiwa Kewirausahaan Ibu-Ibu PKK Desa Belik Melalui Diversifikasi Produk Wingko Nanas - Insania Rizkyning Praja; Kusuma Arum Diana Kumara; Antonius Edi Nugroho (Universitas Negeri Semarang, 2025)
This community service aims to foster an entrepreneurial spirit through optimizing community creativity in processing pineapple into processed products. This community service uses a training method targeting PKK mothers in Belik Village, Belik District, Pemalang Regency. The training activity was carried out on June 30, 2024 at the Belik Village Hall. The PKK mothers were very enthusiastic about participating in the pineapple wingko making activity. This was proven by their attention to following the activity until it was finished. The result of this community service was that there was one MSME that succeeded in making pineapple wingko and marketing it in the village environment. Although it is still at the village level, this proves that an entrepreneurial spirit has been built so that it generates additional income. Pineapple is the main agricultural commodity in Belik District which can be developed through diversification of processed products that have high selling value and increase the selling value of pineapple. Pineapples, which are usually sold whole as fruit, are now being developed into pineapple wingko.